Low cost options of carbon sources, gelling agents and supporting materials used for micropropagation of shoot tips of banana cultivar Grand Nain - Abdallah, Hala M; Ali, Mohamed A; Yagoub, Adil Yousif (Gezira Journal of Agricultural Science, 2014)
The high cost of materials used for media preparation is chiefly constituted by gelling agents and sucrose. The objective of this study was to develop efficient micropropagation techniques for the newly released banana cultivar Grand Nain at a low cost by testing different alternatives of carbon sources (sucrose),gelling agents and supporting materials. Three experiments were conducted to test different carbon sources, gelling agents and support matrices.  In the first experiment, different carbon sources were tested. These included the refined imported sugar special for tissue culture from Sigma Company, Kenana (refined local sugar), Alguneid (brown local sugar) and beet crystal imported sugar from the local market. Results showed that all sources of sucrose resulted in the highest number of explants with shoots, however, Alguneid sugar induced significantly higher number of shoots per explants. There was 99.4% reduction in the medium cost compared to the standard medium of Sigma sugar. The second experiment was conducted to test different gelling agents such as corn starch at 50.0g/l plus agar at 3.0 and 4.0 g/l, corn starch at 50.0g/l plus phytagel at 1.25 and 1.5 g/l, respectively. Phytagel at 2.5 g/l and agar at 9 g/l were used as control. Gelling agents did not differ in the percentage of explants with shoots. However, corn starch at 50.0g/l and phytagel at 1.5 g/l resulted in the highest number of shoots which reduced the medium cost by 30.7%. In the third experiment, different supporting materials were used as low cost options including stone matrices, glass beads, cotton fiber and filter paper. Rock stones were the best supporting material in liquid medium for propagation of banana cv. Grand Nain. It resulted in significantly higher percentage of explants with shoots, number of shoots per explant and plant height.   ارتفاع كلفة الزراعة النسيجية النباتية هو السبب في عدم تطبيقها علي نطاق واسع. إن تكلفة المواد الجيلاتينية (الآجار والفايتاجل) والسكر تمثل أكبر تكلفة بين العناصر المكونة للوسط الغذائي. الهدف من هذه الدراسة هو تطوير خيارات اقتصادية لتقنية زراعة الأنسجة للإكثار الدقيق للموز الصنف قراند نين المجاز حديثاً وذلك باختبار بدائل للسكر والمواد الجلاتينية وايجاد مواد داعمة للزراعات النسيجية في الأوساط الغذائية السائلة. أجريت الاختبارات في هذه الدراسة بإستخدام النظام العشوائي الكامل في خمس مكررات وأربع قمم نامية في كل مكرر. تم تنفيذ ثلاث تجارب بهدف خفض تكلفة الاكثار الدقيق للموز الصنف قراندنين. فى التجربة الأولى تم اختبار أربعة مصادر الكربون وهى: سيقما (سكر نقى مستورد خاص بزراعة الأنسجة من شركة سيقما), كنانة (سكر نقى منتج محلياً من شركة سكر كنانة), الجنيد   ( سكر بنى منتج محلياً من مصنع الجنيد) والبنجر( سكر بلورى مستورد). لا توجد فروقات معنوية بين أنواع السكر التي تم اختبارها في النسبة المئوية للقمم النامية للموز التي تم تحفيز نموات جديدة منها وعدد النموات الجديدة (السيقان)، لكن عدد السيقان النامية من كل قمة نامية علي سكر الجنيد أعلي معنويا من أنواع السكر الأخرى. باستخدام هذه البدائل تم تخفيض 99.4% من تكلفة السكر في الوسط الغذائي. أجريت التجربة الثانية لاختبار مواد جلاتينية مختلفة وهى: 50.0 جرام/لتر من نشا الذرة الشامية مع3.0  جرام/لتر و4.0 جرام/لتر اجار,50.0 جرام/لتر من النشأ مع1.25  جرام/لتر و1.5 جرام/لتر فايتاجل, 2.5 جرام/لتر فايتاجل و9 جرام/لتر اجار كشواهد. أوضحت النتائج أن الاحلال الجزئي للمواد الجلاتينية (الفايتاجل والاجار) بمقدار 50.0 جرام/لتر من نشا الذرة الشامية يمكن استخدامه للإكثار الدقيق للموز صنف قراندنين، حيث لا توجد فروقات معنوية بين كل المعاملات في النسبة المئوية لأجزاء الموز التي تم تحفيز نموات جديدة منها وعدد السيقان مع تخفيض 40.7-30.7 %و65.8-54.7 % في كلفة الآجار والفايتاجل علي التوالي. فى التجربة الثالثة تمت زراعة القمم النامية فى وسط غذائي سائل باستخدام دعامات مختلفة وهى: مصفوفات من الحصى, البلى, ألياف قطنية و أوراق الترشيح. أثبتت النتائج أن مصفوفات الحصى هى أفضل الدعامات المختبرة فى الوسط الغذائي السائل.